Biogeography of mutualistic fungi cultivated by leafcutter ants. Issue 24 (2nd December 2017) - Mueller, Ulrich G.; Ishak, Heather D.; Bruschi, Sofia M.; Smith, Chad C.; Herman, Jacob J.; Solomon, Scott E.; Mikheyev, Alexander S.; Rabeling, Christian; Scott, Jarrod J.; Cooper, Michael; Rodrigues, Andre; Ortiz, Adriana; et al.
Abstract: Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta, Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.